Evacuation under limited visibility - Frank, Guillermo Alberto (2015)
A multiplicity of situations can trigger off an evacuation of a room under panic conditions. For "normal" (with "normal" meaning absence of obstacles, perfect visibility, etc.) environmental conditions, the "faster is slower" effect dominates the dynamics of this process. It states that as the pedestrians desire to reach the exit increases, the clogging phenomena delays the time to get out of the room. But, environmental conditions are usually far from "normal." In this work, we consider that pedestrians have to find their way out under low visibility conditions. Some of them might switch to a herding-like behavior if they do not remember where the exit was. Others will just trust on their memory. Our investigation handles the herding and memory effects on the evacuation of a single exit room with no obstacles. We also include a section on how signaling devices affect the evacuation process. Unexpectedly, some low visibility situations may enhance the evacuation performance. This can be resumed as a second paradoxical result, since we demonstrated in an earlier investigation that "clever is not always better"